The Complexity Relationship Among Participation, Human Resources, Value Co-Creation (VCC), and Value Co-Destruction (VCD) into Sustainable Ecotourism in Indonesia - Harwiki, Wiwiek; Haryatil, Eny; Arif , Donny (Journal of Ecohumanism, 2024)
The paper aims to explain the understanding of tourist behavior that participates in realizing sustainable environmental tourism. Specifically, to analyze the relationship between variables of participation, human resource, value co-creation, value co-destruction and sustainable ecotourism. The study used survey approach. Population were local tourist and foreign tourist visited in 5 ecotourism villages in Indonesia such as: East Java, West Java, Central Java, DI Yogyakarta, and Bali during last 3 months. Questionnaires fulfilled by 425 respondents through hybrid: direct questionnaires and google forms in social media. Ecotourism villages selected by cluster random sampling. Data analysis used Partial Least Square (PLS) with Structural Equation Modelling (SEM) to test hypotheses. The results proved when participation increased, thus the value co-creation higher or increasing, but participation is not determining factor of value destruction. Human resources is determining factor in value co-creation as well as into value co destruction. Further the finding emphasize to decreasing value co-destruction into sustainable ecotourism, otherwise to increasing value co-creation. This study would be valuable asset for tourism to maintain ecotourism through involving tourists to participate at tourist destination, to drive the competence of human resources, to create the beneficial values and vice versa to mitigate value of destruction.